Experimental characterization of Mode II fatigue delamination growth onset in composite Joints - Garpelli, Felipe P; González Ramírez, Francis M; Sales, Rita de Cássia M; Arbelo, Mariano A; Shiino, Marcos Y [UNESP]; Resende, Hugo B; Donadon, Maurício V (SAGE Publications, 2022)
In this article, the structural behavior of co-cured composite joint (CC), co-bonded composite joint (CB), and secondary-bonded composite joint (SB) under Mode II fatigue loading was evaluated. Fatigue performance was evaluated in sub-critical strain energy release rate (SERR) associated with Mode II fatigue induced delamination growth onset. Fatigue tests were carried out using the three-point bending End Notched Flexure test setup for different energy ratios. The experimental results are presented in terms of SERR versus number of cycles, and the SERR threshold for no growth is determined (Gth). Fractographic analyses were performed in order to identify the main failure mechanisms related to each joining technology under Mode II. The results indicated an initial cohesive failure followed by an adhesive failure promoted by crack propagation at the interface between the adhesive and the composite adherend on SB and CB samples, through the coalescence of microcracks that promote the adhesive failure process, leading to fiber pull-out from the matrix and cusps formation in the fracture surface. These results explain the low performance behavior observed on SB and CB bonded techniques. It is worth mentioning that the results and behavior observed in this work are valid only for the laminates, adhesives, surface treatment, and environmental conditions tested herein.
Keywords: adhesion; fracture and fatigue; mechanical properties; polymer composites; Thermosetting resins